2008
DOI: 10.1149/1.2986760
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase Diffusion Growth of SiGe Single Crystals under Magnetic Fields

Abstract: The manuscript presents the results of a combined experimental and modeling study on the Liquid Phase Diffusion (LPD) growth of single crystal SixGe1-x on Germanium with and with the application of magnetic fields. Although the LPD process is mainly diffusion driven through out the growth period, strong natural thermosolutal convection occurs in the first five hours of growth, and the growth interface is concave to the melt. Applied rotating and static magnetic fields were considered to examine the growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although bulk growth of Si 1– x Ge x with a homogeneous composition still remains a challenging task, several researchers have attempted to grow a homogeneous Si 1– x Ge x bulk crystal. To grow a homogeneous crystal, the understanding of solute transport in the solution is necessary. Armour et al reported that the dissolution of silicon into the germanium melt was slightly higher with an applied magnetic field compared with that without a field. In the vertical gradient freezing method, as the crystal growth proceeds, the growth interface shifts toward the high-temperature region, which causes a gradual increase in the temperature of the growth interface; the corresponding composition varies along the solidus line of the Si–Ge binary phase diagram. Thus, control of the temperature at the growth interface is required and is the key factor in obtaining a homogeneous crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Although bulk growth of Si 1– x Ge x with a homogeneous composition still remains a challenging task, several researchers have attempted to grow a homogeneous Si 1– x Ge x bulk crystal. To grow a homogeneous crystal, the understanding of solute transport in the solution is necessary. Armour et al reported that the dissolution of silicon into the germanium melt was slightly higher with an applied magnetic field compared with that without a field. In the vertical gradient freezing method, as the crystal growth proceeds, the growth interface shifts toward the high-temperature region, which causes a gradual increase in the temperature of the growth interface; the corresponding composition varies along the solidus line of the Si–Ge binary phase diagram. Thus, control of the temperature at the growth interface is required and is the key factor in obtaining a homogeneous crystal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the production of bulk SiGe single crystals with desired crystal compositions is problematic due to the large miscibility gap inherent to the alloy. A solution growth technique called Liquid Phase Diffusion (LPD) has been developed to produce graded composition bulk Germanium rich SiGe crystals (1,(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%